2017
DOI: 10.1177/0003319717728226
|View full text |Cite
|
Sign up to set email alerts
|

FABP4 and Cardiovascular Events in Peripheral Arterial Disease

Abstract: Fatty acid-binding protein 4 (FABP4) is a possible biomarker of atherosclerosis. We evaluated FABP4 levels, for the first time, in patients with peripheral artery disease (PAD) and the possible association between baseline FABP4 levels and cardiovascular events over time. Patients (n = 327; mean age 69 ± 10 years) with stable PAD were enrolled in this study. Serum FABP4 was measured by bead-based multiplex assay. Cardiovascular events were analyzed by FABP4 tertiles using Kaplan-Meier and Cox regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…The 18 articles that were not selected studied α-defensin, 21 matrix metalloproteinase 10, 59 galectin-3, 60 soluble tumor necrosis–like weak inducer of apoptosis, 61 ferritin, 62 activated protein C–protein C inhibitor complex, 63 angiopoietin-related growth factor, 64 fatty acid–binding protein 4, 65 alkyl-phosphatidylcholine and alkenylphosphatidylcholine lipids, 66 high-density lipoprotein cholesterol, 66 malondialdehyde-modified low-density lipoprotein, 67 lipoprotein-associated phospholipase A2, 68 cardiac troponin I, 69 phosphate, 70 carboxy-terminal telopeptide of type I collagen, 15 cholinesterase, 71 eicosapentaenoic acid/arachidonic acid ratio, 72 or endothelin-1. 73 …”
Section: Resultsmentioning
confidence: 99%
“…The 18 articles that were not selected studied α-defensin, 21 matrix metalloproteinase 10, 59 galectin-3, 60 soluble tumor necrosis–like weak inducer of apoptosis, 61 ferritin, 62 activated protein C–protein C inhibitor complex, 63 angiopoietin-related growth factor, 64 fatty acid–binding protein 4, 65 alkyl-phosphatidylcholine and alkenylphosphatidylcholine lipids, 66 high-density lipoprotein cholesterol, 66 malondialdehyde-modified low-density lipoprotein, 67 lipoprotein-associated phospholipase A2, 68 cardiac troponin I, 69 phosphate, 70 carboxy-terminal telopeptide of type I collagen, 15 cholinesterase, 71 eicosapentaenoic acid/arachidonic acid ratio, 72 or endothelin-1. 73 …”
Section: Resultsmentioning
confidence: 99%
“…Tuncman et al provided genetic support for the involvement of A-FABP in atherosclerosis in humans, where a reduction in A-FABP activity generated a metabolically favorable phenotype 29 while Furuhashi et al showed that inhibiting A-FABP is effective against severe atherosclerosis and type 2 diabetes in mice 30 . Human studies showed an association between A-FABP and coronary heart disease 31 and has also been shown to be associated with peripheral arterial disease 32 . According to one study, A-FABP reduces the expression of leptin in mice adipocytes 33 , while another study in leptin deficient mice showed an impaired gene expression for lipid utilization for, amongst other proteins, A-FABP 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with TWEAK, preclinical evidence supports a cardioprotective role for PON3 (which was also independently associated with incident HF in the multivariable model). FABP4 is predominantly expressed in macrophages and adipose tissue where it regulates fatty acids storage and lipolysis; FABP4 is also an important mediator of inflammation that has been associated with higher risk of cardiovascular events 60,61 . RARRES2 (or chemerin) is an adipose-derived signalling molecule that regulates adipogenesis and adipocyte metabolism, and it has also been associated with higher risk of cardiovascular events 62,63 .…”
Section: Metabolism Clustermentioning
confidence: 99%